MediaAudiovisual Efektif Meningkatkan Pengetahuan tentang Hygiene Sanitasi dan Keselamatan Kerja Penjamah Makanan - Damayanti, Amilia Yuni; Abidah, Yusrina Husnul; Khofifah, Khofifah; Bilqis, Asyun; Sukowati, Dewi; Dwi, Martinta; Zahraturrosidah, Zahraturrosidah (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
Occupational health and safety as well as hygiene and sanitation are important aspects related to food management. This aspect affects food quality and worker safety so that food can be consumed safely and food handlers do not experience any work accidents. One of the efforts made to emphasize occupational health and safety as well as hygiene and sanitation is by educating food handlers. This education aims to determine the effectiveness of counseling using audiovisual methods in increasing information related to occupational health and safety as well as hygiene and sanitation for food handlers. This training used a quasi-experimental method to design a pretest-posttest panel with a sample of eight food handlers. The questionnaire was used to collect pre-test and post-test results and then tested using the paired t-test and calculated through SPSS 24.0. After carrying out this activity, it was discovered that counseling through audiovisual methods could effectively increase hygiene, knowledge of sanitation, and work safety for food handlers (p0.05) by 12%